The Importance of Legal Education in Creating a Harmonious Society Obeying the Law in Indonesia - Ririn Kurniasi; Alfred Yetno (International Proceeding On Religion, Culture, Law, Education, And Hindu Studies, 2022)
Lack of understanding to obey the legal rules that apply in Indonesia from some communities because these communities do not yet have a strong legal awareness so that these people do not really understand the meaning of every legal regulation that exists in Indonesia and there are even some people who do not know the existence of legal regulations certain that are implemented by the Government of Indonesia. Based on this, we can learn that there are still many violations of the rule of law by some people in Indonesia not because of the community's intention but because of the public's ignorance of the purpose of the existing legal regulations in Indonesia. Violations of the rule of law that occur intentionally are not carried out by the Indonesian people who actually already have good knowledge and knowledge of the law but still violate the law. To prevent this from happening, the Indonesian government is obliged to provide knowledge about legal education to all Indonesian people and from legal education it can increase understanding of the importance of legal education for the Indonesian people so that a harmonious Indonesian society can obey the law in Indonesia.